Trends of Transmitted and Acquired Drug Resistance in Europe From 1981 to 2019: A Comparison Between the Populations of Late Presenters and Non-late Presenters - Miranda, Mafalda N. S.; Pingarilho, Marta; Pimentel, Victor; Martins, Maria do Rosário O.; Kaiser, Rolf; Seguin-Devaux, Carole; Paredes, Roger; Zazzi, Maurizio; Incardona, Francesca; Abecasis, Ana B. (Frontiers in Microbiology, 2022)
Background: The increased use of antiretroviral therapy (ART) decreased mortality and morbidity of HIV-1 infected people. Increasing levels of HIV drug resistance threatens the success of ART regimens. Late presentation, on the other hand, can impact on treatment outcomes, health costs and potentiate transmission of HIV. Objective: To describe the patterns of transmitted drug resistance (TDR) and acquired drug resistance (ADR) in HIV-1 infected patients followed in Europe, to compare its patterns in late presenters (LP) vs non-late presenters and to analyze the most prevalent drug resistance mutations among HIV-1 subtypes. Methods: Our study includes clinical, socio-demographic and genotypic information from 26973 HIV-1 infected patients from the EuResist Integrated Database (EIDB) between 1981 and 2019. Results: Among the 26973 HIV-1 infected patients included in the analysis, 11581 (42.9%) were ART-naïve patients and 15392 (57.1%) were ART-experienced. The median age was 37 (IQR: 27.0-45.0) years old and 72.6% were males. The main transmission route was through heterosexual contact (34.9%) and 81.7% of patients were originated from Western Europe. 71.9% of patients were infected by subtype B and 54.8% of patients were classified as LP. The overall prevalence of TDR was 12.8% and presented an overall decreasing trend (p for trend<0.001), as for ADR prevalence was 68.5% also with a decreasing trend (p for trend<0.001). For LP and NLP, TDR was 12.3% and 12.6%, respectively, while for ADR 69.9% and 68.2%, respectively. The most prevalent TDR drug resistance mutations, in both LP and NLP, were K103N/S, T215rev, T215FY, M184I/V, M41I/L, M46I/L and L90M. Conclusion: Our study showed that the overall TDR (12.8%) and ADR (68.5%) presented decreasing trends in the study time period. For LP, the overall TDR was slightly lower than for NLP (12.3% vs 12.6%, respectively); while this pattern was opposite for ADR (LP slightly higher than NLP). We suggest that these differences, in the case of TDR, can be related to the dynamics of fixation of drug resistance mutations; and in the case of ADR with the more frequent therapeutic failure in LPs.